2017
DOI: 10.18547/gcb.2017.vol3.iss3.e31
|View full text |Cite
|
Sign up to set email alerts
|

DEgenes Hunter - A Flexible R Pipeline for Automated RNA-seq Studies in Organisms without Reference Genome

Abstract: Differential gene expression based on RNA-seq is widely used.Bioinformatics skills are required since no algorithm is appropriate for all experimental designs.Moreover, when working with organisms without reference genome, functional analysis is less than straightforward in most situations. DEgenes Hunter, an attempt to automate the process, is based on two independent scripts, one for differential expression and one for functional interpretation. Based on replicates, the R script decides which of the edgeR, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Therefore, in order to obtain an accurate mapping of generated reads, we used as reference our recently reported species-specific transcriptome of Citrus aurantifolia [26], and the corresponding orthologs were annotated from A. thaliana TAIR10 database. Then, we carried out a differential expression analysis by means DEgenes-Hunter [28]. A principal component (PC) analysis showed a correlation between biological replicates demonstrating the reliability and consistency of transcriptional data (Figure 4).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, in order to obtain an accurate mapping of generated reads, we used as reference our recently reported species-specific transcriptome of Citrus aurantifolia [26], and the corresponding orthologs were annotated from A. thaliana TAIR10 database. Then, we carried out a differential expression analysis by means DEgenes-Hunter [28]. A principal component (PC) analysis showed a correlation between biological replicates demonstrating the reliability and consistency of transcriptional data (Figure 4).…”
Section: Discussionmentioning
confidence: 96%
“…Transcript counts were obtained using Sam2count.py. Data normalization and differential expression studies were carried out using DEgenes-Hunter [28] with EdgeR and DESeq2 package; any differentially expressed candidate gene must appear in both algorithms with |log2ratio| ≥ 1 and false discovery rate (FDR) <0.05. Enriched gene ontology term annotations were identified using Singular Enrichment Analysis (SEA) in agriGO v.2 [29].…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…Finally, its suitability for RNA-seq studies was demonstrated using an experimental study that investigates the role of RA on metamorphic larvae by using a specific RA-receptor agonist or a RA synthesis blocker. The bioinformatic analysis was performed using an improved version of DEGenes Hunter 30 .…”
mentioning
confidence: 99%
“…Samtools (v.0.1.19) quantified known transcripts (count reads per transcripts) ( 53 ), and transcripts were annotated using Full-Lengther-Next ( 54 ). Statistical comparisons of transcript expression between diet groups and between atopic and healthy dogs were performed using DEgenes-Hunter (v.2.0.11) ( 55 ), a tool that imputes raw read counts generated by Bowtie2/Samtools into the EdgeR ( 56 ) and DESeq2 ( 57 ) algorithms. Fold change (FC) ≥2, and a false discovery rate (FDR) corrected p < 0.05 were set as thresholds.…”
Section: Methodsmentioning
confidence: 99%